Students' obstacles in solving mathematical literacy problems using the onto-semiotic approach - Amanda, Adelia Tria; Hidayanto, Erry; Hafiizh, Mochammad (Jurnal Gantang, 2026)
Mathematical literacy is crucial for students, requiring both an understanding of mathematical concepts and the ability to apply them in solving diverse problems. However, students frequently encounter difficulties with mathematical literacy tasks, particularly those involving proportions, which may constitute learning obstacles. This study aims to identify and analyze students' learning obstacles in the context of mathematical literacy on the topic of proportions using an onto-semiotic approach. Qualitative research with a phenomenological approach was employed in this study, involving 27 eighth-grade students at a State Junior High School in Ngoro. Data collection techniques include tests, interviews, and documentation studies. Data analysis consisted of three stages: reduction, presentation, and conclusion. This study reveals three types of learning obstacles among students: (1) epistemological obstacles, which arise from students' limited understanding of concepts related to proportion; (2) ontogenic obstacles, which occur due to a leap in students' cognitive transition; and (3) didactical obstacles, which are caused by procedural teaching methods. Based on the onto-semiotic approach, the students had difficulty understanding mathematical language, defining mathematical ideas, applying the property of proportion, and performing appropriate procedures. This study provides insights that may assist teachers in designing more effective instructional strategies.